An Investigation of the Use of Grammatical Cohesive Devices in Grade 11 L2 Learners at a Private School in RAK, UAE - ABUALLAIL, KAMEL RABEA (2020)
Writing has always been regarded as the most challenging language skill for the majority of L2 learners. Several studies have found that L2 learners encounter difficulties in implementing cohesive devices in a way that enable them to produce coherent written texts. Research has proved that these difficulties are reflected on the misuse, overuse or underuse of cohesive devices, which maintain cohesion and coherence in a text. This study is an investigation of the use of grammatical cohesive devices in grade 11 L2 learner’s descriptive essays at a private school in RAK, UAE. This study focuses on identifying the frequency of occurrence of four grammatical cohesive devices including reference, conjunction, ellipsis and substitution in L2 students’ descriptive essay writing. It also investigates the correlation between the number of used grammatical cohesive devices and the quality of writing. Furthermore, the study identifies the difficulties encountered by L2 learners in respect of using cohesive grammatical devices in writing. In order to achieve the purpose of the study and answer the research questions, a mixed-method approach has been adopted. The quantitative method approach was used to find out the frequency of each grammatical cohesive device in 44 descriptive essays. To examine the correlation between the number of used grammatical devices and the quality of writing, the quantitative descriptive statistics approach using Pearson Correlation Coefficient, was implemented. However, the qualitative descriptive approach was implemented in terms of semi-structured interviews conducted for 4 teachers and 10 students to identify the difficulties that encounter L2 learners regarding using grammatical cohesive devices in writing. An analysis of the quantitative and qualitative research methods applied in the study demonstrated that reference is the most frequently used cohesive device in students’ writing, followed by conjunction. Ellipsis was proved to be the third most frequently used cohesive device. Substitution came the fourth most frequently used cohesive device. A moderate positive association between the total number of grammatical cohesive devices used and L2 learners’ marks was proved by Pearson Correlation Coefficient. The participants faced some hindrances regarding using grammatical cohesive devices such as concentrating on specific types and ignoring other types such as ellipsis and substitution. Students also encountered the difficulty of dealing with grammatical cohesive devices as grammar and vocabulary items and not including them in contexts to be practiced in the writing procedure. Learners also faced another difficulty represented by the lack of feedback given by teachers on their writing concerning grammatical cohesive devices. As a recommendation of the study, teachers are recommended to include grammatical cohesive devices in the context of reading and writing. Teachers are also recommended to include grammatical cohesive devices in the writing rubric. Furthermore, learners are recommended to raise their awareness regarding interference of L1 through practicing varied language activities such as reading and listening.